MODE OF PRODUCTION IN FISHERMEN COMMUNITY: CASE STUDY OF RELATIONSHIP BETWEEN THE SHIP OWNER AND LABOUR OF FISHERMEN IN PULAU BAAI AREA, BENGKULU CITY - Elia Damayanti; Septri Widiono; Satria Putra Utama (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
Modernization in catch fisheries sector by mean machinary application for fishing could be devided into some phases. Every phases showed some production relation between the ship owners and their labours. In the Marxist tradition of thought, the study about these relationship could be gained by elaborate the mode of production. For more specific, this study were elaboratethe mode of production in every phases of modernization. Mode of production consisted force of production and relation of production. In this context, force of production was mean of production like ships, net and seine. While relation of production wasthe organization of fishermen, power and control by the owners to their labours. The study was conducted by using qualitative method so depth interviewed of some key informants had been main method in collecting datas. The results of the study indicated that fisheries modernization in research area held into four phases. We called them as period oflancang, trawl, bagan, and purseseine. Further more, the mode of production in every phases as follow namely, lancang was subsistence production, trawl was commercialist production, and bagan was commercialist production. While purseseine had has two mode of production, namely commercialist production for Bengkulu’s owner and capitalist production for Chinese’s owner.Keywords : mode of production, Pulau Baai, Lancang, Trawl, Bagan, and Purse Seine.